Strategi branding dan positioning produk perbankan syariah di Indonesia - Marpaung, Reza Rahmad (Maliki Interdisciplinary Journal, 2025)
Islamic banking in Indonesia has shown significant growth since the establishment of Bank Muamalat Indonesia in 1992. Despite having strong roots in Islamic teachings, these financial institutions attract interest not only from the Muslim community but also from non-Muslims, reflecting the universal appeal of sharia principles in finance. To remain competitive, Islamic banks need to implement innovative branding and positioning strategies. This research uses a qualitative method with a literature review to analyze various related literatures. The results show that proper market segmentation, targeting and positioning are essential in creating a strong brand image. Product and service differentiation is also key to attracting customers and maintaining their loyalty. Thus, a branding strategy that is adaptive and responsive to market dynamics is necessary for Islamic banking to continue to grow and contribute to the Indonesian economy.